Complex Care Curriculum: Autonomic Dysreflexia - Jimmy Beck; Rebekah Conroy (Association of American Medical Colleges, 2015)
Abstract Introduction Children with special health care needs are increasingly prevalent in US hospitals. The pediatric hospitalist is often the primary provider of inpatient care for these patients. However, exposure to this patient population during training varies from provider to provider. The purpose of this project is to provide a multimodal educational curriculum for health care providers with the overall goal of improving inpatient care for this at-risk population. The Complex Care Curriculum is primarily composed of a series of topic-specific learning modules. Methods This particular resource was created to provide pediatricians with educational materials related to the care of the medically complex child with autonomic dysreflexia (AD), which is a clinical phenomenon with life threatening potential that affects patients with spinal cord injuries above the T-6 Level. The incidence of AD is reported in the literature to affect approximately 16% of children and adolescents with spinal cord injuries. This resource includes a multimedia, narrated PowerPoint presentation for asynchronous learning, a PowerPoint presentation adapted for didactic teaching, as well as accompanying facilitator guides, suggested multiple-choice questions with answer key, and an evaluation tool. Results This curriculum, including this specific learning activity, was first launched at Children's National Medical Center in Washington, DC in February 2012. Preliminary data from eight participants of this particular module showed 100% of participants agreed or strongly agreed that the learning activity met the stated learning objectives; the material was engaging and interesting, was relevant to clinical practice, and increased comfort with teaching about this topic; and, the format of this learning activity was appropriate for learning needs. The mean score on the pretest was 45% and increased to 86% on the posttest (p = .072). Comments about what participants liked most about this learning module included: "concise," "straight forward explanations," and "description of pathophysiology and why autonomic dysreflexia occurs." Discussion Asynchronous learning modules, utilized appropriately, can augment learning by providing individualized instruction and mastery of fundamentals. Based on this study, this module along with others in the curriculum continues to be offered to trainees and new faculty to augment their knowledge and skills in this area.